A myth of soft budget constraints in socialist economies - Vladimir V. Popov (Transformation, Integration and Globalization Economic Research (TIGER), 2020)
Most of the time the budget constraints in the socialist economies were harder than in developing countries and no less hard than in developed countries. The soft budget constraints (SBC) in socialist economies were not pervasive, as most authors believe, but selective, i.e. involved subsidization of some enterprises/industries at the expense of the other. This type of selective subsidization is a classic case of industrial policy: it may be good or bad, leading to success (China, Vietnam) or failure (USSR, Eastern Europe), but cannot be regarded as an intrinsic feature of the socialist centrally planned economy and an example of pervasive SBC. Pervasive SBC should be associated with permanent government budget deficit, debt accumulation, high inflation and other forms of macroeconomic populism. In the Soviet Union in the post-war period (after the monetary reform of 1947 and until the Gorbachev financial and monetary expansion that started in 1987) budget deficit and debt were very low, open and hidden inflation was less than several percent a year - a better record than in most Western countries. But in the 1990s in Russia, other former Soviet republics and most East European countries budget constraints were weakened dramatically and inflation increased to hundreds and thousands percent a year. SBC is just one type of this populist macroeconomic policy that was rare in socialist countries, but is found in abundance in many developing countries (especially Latin America and Sub-Sahara Africa) and transition economies (especially FSU states).
Keywords: H6; O25; P34; P35; P40; P43; 330; Soft budget constraints; socialist economies; industrial policy